The Effect of Significant IPO Firms on Industry Incumbents: Evidence from Tax Planning - Chyz, James; Henry, Erin; Omer, Thomas; Wu, Biyu (Management Science, 2023)
An IPO is a significant event for an individual firm, and the literature examining initial public offering (IPO) firms is extensive. However, there is little evidence on the subsequent effect of a significant IPO on incumbent firms. We extend this literature by using firms’ tax policies as a powerful setting to identify whether incumbent firms respond to a significant IPO in their industry. Specifically, we use a first difference analysis to examine whether incumbent firms herd their effective tax rates (ETRs) toward a significant IPO’s ETR. We provide robust evidence that incumbent firms adjust their ETR either up or down by one to two percentage points, on average, for up to three years following a significant IPO entrance to the industry. Cross-sectional analyses support attention-based and tax-specific motives for herding, and additional analysis documents market attention-based consequences. Finally, we find that incumbents weigh the benefits of herding against the cost of adjusting their ETR and that incumbent firms use discretionary tax accruals as a less costly mechanism to imitate IPO firms’ generally accepted accounting principles (GAAP) ETRs. We contribute to an IPO literature that focuses almost exclusively on the IPO firm. We extend the literature by providing evidence that a significant IPO in an industry can result in a herding response in incumbent firms’ policy choices. This paper was accepted by Brian Bushee, accounting. Funding: T. Omer acknowledges funding from the Delmar Lienemann Sr. Chair of Accounting at the University of Nebraska–Lincoln. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2022.4573 .